2019
DOI: 10.1002/jcb.29397
|View full text |Cite
|
Sign up to set email alerts
|

The anticancer effect of the TLR4 inhibition using TAK‐242 (resatorvid) either as a single agent or in combination with chemotherapy: A novel therapeutic potential for breast cancer

Abstract: Increasing pieces of evidence indicate that inflammatory processes facilitate tumorigenesis; tumor cells simulate the mechanisms by which innate immune cells produce pro‐inflammatory cytokines to exploit them for their own survival and proliferation. Toll‐like receptor 4 (TLR4), which serves as one of the most well‐known receptors on the surface of the immune cells, is often expressed ectopically in the tumor cells resulting in tumor progression, invasion, and chemoresistance. In this study, we examined the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 49 publications
(90 reference statements)
3
15
0
Order By: Relevance
“…SM934, a derivative of another anti-malarial drug artemensin can inhibit the proliferation and metastasis in breast cancer probably via inhibition of TLR signaling [52]. TAK-242 specifically inhibits TLR-4 by binding to cysteine 747 in the intracellular domain and consequently suppresses the progression of breast cancer [53]. Therapeutic role of SM934, another artemensin derivative has been well documented in inflammatory disease [54], but its role in cancer prevention is still need to be explored.…”
Section: Tlrs Modulation In Cancer Treatmentsmentioning
confidence: 99%
“…SM934, a derivative of another anti-malarial drug artemensin can inhibit the proliferation and metastasis in breast cancer probably via inhibition of TLR signaling [52]. TAK-242 specifically inhibits TLR-4 by binding to cysteine 747 in the intracellular domain and consequently suppresses the progression of breast cancer [53]. Therapeutic role of SM934, another artemensin derivative has been well documented in inflammatory disease [54], but its role in cancer prevention is still need to be explored.…”
Section: Tlrs Modulation In Cancer Treatmentsmentioning
confidence: 99%
“…Furthermore, a GWAS study on primary biliary cirrhosis (PBC) patients has revealed that PDGFB was the only transcript regulated by risk variants of TLR4 signaling (Kim et al, 2014). But more importantly, TLR4/PDGF interactions have been reported in malignant tissues, since they share common ligands (e.g., HIF‐1α) and downstream transcription factors (e.g., c‐Myc) that could potentially cause feedback loops (Han et al, 2016; Moench et al, 2016; Zandi, Kashani, Bashash, et al, 2019).…”
Section: The Tlr4 Pathway Has Signaling Crosstalk With Various Growthmentioning
confidence: 99%
“…Inline, it has been reported that the activation of TLR4 with LPS induced resistance of human colon and pancreatic cancer cells to TRAIL‐induced apoptosis in an NF‐кB‐dependent manner (Beyer et al, 2017; Tang & Zhu, 2012). Besides, it has been revealed that the inhibition of TLR4 using small molecule inhibitor TAK‐242 suppressed NF‐кB‐related antiapoptosis genes BCL‐xL, BCL‐2, and survivin in breast and ovarian cancer cells and led to increased apoptosis (Kashani, Zandi, Bashash, et al, 2019; Zandi, Kashani, Bashash, et al, 2019). In an interesting study, it was shown that after treating colon cancer cells with oxaliplatin and 5‐fluorouracil, the stimulation of TLR4 led to the phosphorylation of GSK3β, overexpression of Bcl‐2 family and multidrugs resistance proteins, and significant inhibition of apoptosis (Chung & Kim, 2016).…”
Section: Tlr4 Plays Various Roles In Different Aspects Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Recently, it became evident that this inhibitor has significant anti-tumor capacity. TAK-242 exerted a favorable effect in ovarian 18 and breast cancer cells 19 through regulating the expression of both NF-κBand p53-dependent apoptotic target genes. TAK-242 also prevented the epithelial-mesenchymal transition of ovarian and breast cancer cells by reducing the enzymatic activity of matrix metalloproteinase 2 and 9.…”
Section: Tlr Antagonists and Cancer Treatmentmentioning
confidence: 99%